2020
DOI: 10.1186/s12902-020-00562-z
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between obesity, diabetes, hypertension and vitamin D deficiency among Saudi Arabians aged 15 and over: results from the Saudi health interview survey

Abstract: Background: Obesity and diabetes are related conditions, the prevalence of which has increased globally in recent years. These conditions have been linked to hypertension and vitamin D deficiency though the nature of the relationship remains unclear and is likely to vary between identifiable groups and specific contexts. The aim of this paper is to examine the relationships between obesity, type 2 diabetes, hypertension and vitamin D, among Saudis citizens aged 15 and over. Methods: Self-reported and measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“…WC was an important indicator of central obesity. Previous studies (46,47) indicated that the risk of hypertension in centrally obese patients was much higher than that of the normal population. Therefore, WC was also an important risk factor for hypertension.…”
Section: Discussion Principal Findingsmentioning
confidence: 94%
“…WC was an important indicator of central obesity. Previous studies (46,47) indicated that the risk of hypertension in centrally obese patients was much higher than that of the normal population. Therefore, WC was also an important risk factor for hypertension.…”
Section: Discussion Principal Findingsmentioning
confidence: 94%
“…10 Another Saudi study reported the association of hypertension, DM, and obesity, and around 70% of their study participants, aged 15 or above, were found to be obese. 11 The overall incidence of obesity in Saudi Arabia is 35.4%, which is much higher than that of neighboring Arab countries. 12 Another previous study from our university has reported irregular dietary patterns and most university students' sedentary lifestyles.…”
Section: Discussionmentioning
confidence: 98%
“… 10 Another Saudi study reported the association of hypertension, DM, and obesity, and around 70% of their study participants, aged 15 or above, were found to be obese. 11 …”
Section: Discussionmentioning
confidence: 99%
“…The direct and indirect role of VDD in the regulation of sleep could be related to disturbance of involved hormones (Mergl et al, 2021). Vitamin D receptors and enzymes that control their activation and degradation are expressed in several areas of the brain involved in sleep regulation, Vitamin D is also involved in the pathways of production of melatonin hormone involved in sleep regulation (Al-Sumaih et al, 2020).…”
Section: Resultsmentioning
confidence: 99%